Association between non-reporting of accident and contributing factors in Malaysia’s construction industry - Ab Hadi, Nur Adilla; Md Tamrin, Shamsul Bahri; Ng, Yee Guan; Vivien, How; Abd Rahman, Rozana (Japan Ergonomics Society, 2017)
Malaysian construction sector is one of the critical sectors represented by high accident and fatality rates over time. Accident rate in the construction sector is the third highest in Malaysia and the highest for fatality cases. Construction’s workers came in contact with dangerous equipment and substances which can easily affect their physical and health condition. The increasing development of construction industries raise the probability of hazard exposure and accident occurrence. The goal of the study is to determine the association between non-reporting of accident in construction industries and the factors related with the occurrence of reporting trend. A cross sectional study design was conducted in twelve (12) construction sites of big construction company in Klang Valley and Johor Bahr, Johore by adopting stratified sampling method with the participation of 1598 respondents from selected sites. The data was collected through interview session using self-constructed questionnaire to determine the accident occurrence, reporting behavior, type of common accidents as well as the possible causal factors for under reporting cases. The study revealed the prevalence of non-reporting of accident in construction industries. (94.7%) of the construction workers did not report the accident while (5.3%) did report the accident. Chi square test revealed a significant statistical association between the Occupational Safety Health Management System (OSHMS) and non-reporting of accident. Induction training related to OSH from employer before employee start the work (X2=7.018, p= 0.030) and the awareness of the workers of the risk at the company (X2=8.278, p= 0.016) show significance association with the prevalence of non-reporting of accident. The result from this study, indicates that there was significant association between the Safety and Occupational Health Practices in the involvement of the workers in OSH activities (X2=7.108, p = 0.029) in non-reporting of accident. Based on the findings, further study should be conducted to determine more factors related to non-reporting among workers and a formulation on calculating non-reporting should be developed.